Opportunities and constraints in agriculture: A gendered analysis of cocoa production in Southern Cameroon - Wokia-azi N. Kumase; Herve Bisseleua; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
In this paper we examine gender differences in cocoa production in Cameroon using a survey of about 1000 cocoa producers in Southern Cameroon. We find that women farmers have access to land (of similar size to men), but through different mechanisms than men. They are strongly disadvantaged when it comes to access to extension services and marketing and control of proceeds. Despite these disadvantages, the productivity in terms of output per unit of land is similar to that of their male colleagues. Productivity analyses suggest that a slight disadvantage in productivity on female plots turns into a slight advantage when controlling for all the factors affecting productivity. The policy message from this is quite clear: Independent women farmers are a reality in Cameroon that need equal access to inputs and technologies, and support. If given equal opportunities, their productivity is at least as high as that of men.
Keywords: J71; Q12; O13; 330; Gender inequality; cocoa farming; Cameroon